Cycling-based repeat sprint training in the heat enhances running performance in team sport players - Gale, R. M.; Etxebarria, N.; Pumpa, K. L.; Pyne, D. B. (European Journal of Sport Science, 2021)
Applying heat training interventions in a team sports setting remains challenging. This study investigated the effects of integrating short-term, repeat sprint heat training with passive heat exposure on running performance and general conditioning in team sport players. Thirty male club-level Australian Football players were assigned randomly to: Passive + Active Heat (PAH; n = 10), Active Heat (AH; n = 10) or Control (CON; n = 10) to complete 6 × 40 min high-intensity cycling training sessions over 12 days in 35°C (PAH and AH) or 18°C (CON), 50% RH in parallel with mid-season sports-specific training and games. Players in PAH were exposed to 20 min pre-exercise passive heat. Physiological adaptation and running capacity were assessed via a treadmill submaximal heat stress test followed by a time-to-exhaustion run in 35°C, 50% RH. Running capacity increased by 26% ± 8% PAH (0.88, ±0.23; standardised mean, ± 90% confidence limits), 29% ± 12% AH (1.23, ±0.45) and 10% ± 11% CON (0.45, ±0.48) compared with baseline. Both PAH (0.52, ±0.42; standardised mean, ± 90% confidence limits) and AH (0.35, ±0.57) conditions yielded a greater improvement in running capacity than CON. Physiological and perceptual measures remained relatively unchanged between baseline and post-intervention heat stress tests, within and between conditions. When thermal adaptation is not a direct priority, short-term, repeat effort high-intensity cycling in hot conditions combined with sports-specific training can further enhance running performance in team sport players. Six heat exposures across 12-days should improve running performance while minimising lower limb load and cumulative fatigue for team sports players.